Macroeconomic Policies Interaction & the Symmetry of Financial Markets' Responses - Muhammad Ali Nasir; Alaa M. Soliman; Milton Yago; Junjie Wu (Journal of Central Banking Theory and Practice, 2016)
This concise study analyses the symmetry of financial markets' responses to macroeconomic policy interaction in the United Kingdom. Employing the Vector Auto-regression (VAR) model on monthly data of the British financial sector and macroeconomic policies from January 1985 to August 2008, this study found that the equity and sovereign debt markets showed identical symmetry in response to macroeconomic policy interaction.
Keywords: E44; E61; G12; G18; 330; Financial Markets; Macroeconomic Policy Interaction; Symmetry of financial markets responses